Theta Activity in the Left Dorsal Premotor Cortex During Action Re-Evaluation and Motor Reprogramming - Pellegrino, Giovanni; Tomasevic, Leo; Herz, Damian Marc; Larsen, Kit Melissa; Siebner, Hartwig Roman (Frontiers in Human Neuroscience, 2018)
The ability to rapidly adjust our actions to changes in the environment is a key function of human motor control. Previous work implicated the dorsal premotor cortex (dPMC) in the up-dating of action plans based on environmental cues. Here we used electroencephalography to identify neural signatures of up-dating cue-action relationships in the dPMC and connected frontoparietal areas. Ten healthy subjects performed a pre-cued alternate choice task. Simple geometric shapes cued button presses with the right or left index finger. The shapes of the pre-cue and go-cue differed in two third of trials. In these incongruent trials, the go-cue prompted a re-evaluation of the pre-cued action plan, slowing response time relative to trials with identical cues. This re-evaluation selectively increased theta band activity without modifying activity in alpha and beta band. Source-based analysis revealed a widespread theta increase in dorsal and mesial frontoparietal areas, including dPMC, supplementary motor area, primary motor and posterior parietal cortices. Theta activity scaled positively with response slowing and increased more strongly when the pre-cue was invalid and required subjects to select the alternate response. Together, the results indicate that theta activity in dPMC and connected frontoparietal areas is involved in the re-adjustment of cue-induced action tendencies.